MENINGKATKAN KEMANDIRIAN SISWA DALAM PEMBELAJARAN BAHASA MELALUI PEMBELAJARAN BERBASIS KOMPUTER COMPUTER ASSISTED LANGUAGE LEARNING (CALL) - Wulandari, Ella (MAJALAH ILMIAH PEMBELAJARAN, 2008)
In addition to that, learner’s autonomy indicated by learner’s ability in collaborating with peers independently brings significant effect on maximizing the zone of proximal development of the learner ’s. The zone of proximal development is at its best when learner is able to acquire language input which is a step beyond his present language competence. Despite those two huge benefits of developing /earner’s autonomy, teacher ·s· centredness has still, unfortunately, been dominating the teaching and learning practices in Indonesian schools. One of the effective attempts to reduce teacher’s centredness and build learner’s and teacher’s autonomy is Computer Assisted Language Learning (CALL). By considering the principles in bui!ding learner’s autonomy and the characteristics of CALL, this paper is aimed at highlighting the significant correlation between /earner’s autonomy and CALL and the possibilities or criteria in combining the two so as 10 create an effective language teaching in classroom.